Peningkatan Kualitas Bahan Bakar Biogas Melalui Proses Pemurnian Dengan Zeolit Alam - Hamidi, Nurkholis; Gede Wardana, I Nyoman; Widhiyanuriyawan, Denny (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Brawijaya, 2011)
Biogas from digester consists primarily of methan (CH4) and carbondioxyde (CO2). Trace components that are often present in biogas are water vapor (H2O) , hydrogen sulfide (H2S),hydrocarbons (HC), ammonia (NH3, oxygen (O2), carbon monoxide (CO) and nitrogen (N2). In order to improve the quality of biogas, a cleaning process to remove the trace components and an upgrading process to adjust the calorific value are needed. A number of techniques have been developed to remove the trace components from biogas. In this experiment, however, chemical absorption of CO2 and H2S by solid zeolite in a plastic bag was experimentally investigated. The solid zeolite was activated by heat treatment and KOH. Absorption characteristics were examined. Test results revealed that the solid zeolite used were effective in adsorbed CO2 and H2S in biogas, creating CH4 enriched fuel. Absorption capability was transient in nature. With regular replacement or regeneration of used solid zeolite, upgraded biogas can be maintained. This technique proved to be promising in upgrading biogasquality.Keywords: KOH compound, calorific value of biogas, zeolite.